O-006 Correlation of CT and MRI Clot Characteristics with TICI 3 Reperfusion Using Stent Retrievers in Acute Stroke Intervention. (29th July 2016) - Wong, J; Mlynash, M; Telischak, N; Moraff, A; Do, H; Dodd, R; Heit, J; Marks, M
Abstract : Introduction: Reperfusion to TICI 2 B/3 with stent retrievers has significantly improved when compared with intravenous tPA in several recent randomized controlled trials. However, at least 20% of patients did not achieve this degree of reperfusion. In prior studies, recanalization rates with tPA and early-generation thrombectomy devices (e.g. MERCI) correlated with erythrocyte-rich clots represented by hyperdense MCA (HDMCA) on CT or blooming artifact (BA) on susceptibility-weighted MRI. We hypothesize that clot characteristics, such as clot length, and the presence of HDMCA or BA, may influence the rate of full (TICI 3) reperfusion and the number of passes to achieve reperfusion with stent retrievers. Methods: We retrospectively identified all patients with anterior circulation strokes treated with stent retrievers between January 2015 and March 2016 from our institutional stroke database. All patients underwent a pre-procedural CT or MRI, and revascularization using combined mechanical and aspiration thrombectomy (Solumbra) technique. Patient demographics, risk factors, stroke presentation data, and endovascular treatment details (equipment, number of thrombectomy passes, final TICI reperfusion score, and complications) were recorded. Recorded clot characteristics included the presence of HDMCA and BA on CT and MRI, clot length and Hounsfield Unit density on CT or clot signal intensity on susceptibility-weighted MRI compared to corresponding contralateral artery. Primary outcomes of full reperfusion (TICI 3) and corresponding number of passes were correlated with clot characteristics. Univariate and multivariate analyzes were performed to identify any significant associations. Results: Sixty-four patients with anterior circulation proximal vessel occlusion were treated using stent retrievers. There were 23 (36%) females with a mean age of 73 ± 14 years (Range 28–92 years). Median NIHSS on presentation was 14 (IQR 10–19). Vessel occlusion was localized to the ICA terminus (10 patients, 16%), M1 (41 patients, 64%) and M2 (13 patients, 20%) segments. Intravenous tPA was administered in 44 patients (69%). TICI 2 B/3 reperfusion was achieved in 57 patients (89%) and TICI 3 in 27 (42%). Among HDMCA patients, TICI 3 rate was 50% (vs 36% without HDMCA, p = 0.71); 47% with BA (vs 23% without, p = 0.27); and 49% with HDMCA or BA (vs 29% without, p = 0.13). No statistical difference was detected between the TICI 3 score and other clot characteristics (clot length, absolute and relative clot density or signal intensity). TICI 3 was significantly associated with single pass revascularization (74% vs 41%, p = 0.008), and time from access to revascularization (30 vs 54 minutes, p = 0.004). Longer clot length on CT correlated to a greater number of passes (Spearman's rho = 0.7, p = 0.001) and longer time from access to revascularization (rho = 0.47, p = 0.036). Conclusion: A greater percentage of patients with HMDCA or BA will have full (TICI 3) reperfusion compared to patients without HDMCA or BA, however this study was underpowered to demonstrate these differences were significant. Longer clot length is correlated with a greater number of passes and longer time to revascularization. Disclosures: J. Wong: None. M. Mlynash: None. N. Telischak: None. A. Moraff: None. H. Do: None. R. Dodd: None. J. Heit: None. M. Marks: None.